Computational Fluid Dynamic Modelling and Optimisation of Wastewater Treatment Plant Bioreactor Mixer - Andrew Elshaw; Nur M. S. Hassan; M. Masud K. Khan (Energies, 2018)
This study aims to determine the optimal configuration (position and operation duration) for wall mounted mechanical mixers based on the comparison of three-dimensional computational fluid dynamics (CFD) modelling results and physical data collected from the treatment plant. A three dimensional model of anoxic zone in 1, 2 and 3 of Northern Wastewater Treatment Plant (NWWTP) located at Cairns Regional Council, Cairns, Queensland, Australia was developed and validated. The model was used to simulate the flow pattern of the WWTP and the simulation results are in good agreement with the physical data varying between 0% to 15% in key locations. The anoxic zones were subject to velocities less than the desired 0.3 m per second however results for mixed liquor suspended solids (MLSS) concentration indicate that good mixing is being achieved. Results for suspended solids concentrations suggest that the anoxic zones are towards the upper limits recommended by literature for specific power dissipation. The duration for operation of mechanical mixers was investigated and identified that the duration could be reduced from 900 s down to 150 s. Alternative mixer positioning was also investigated and identified positioning which would increase the average flow velocity with decreased duration (150 s). The study identified that Council may achieve savings of $28,500 per year through optimisation of the mechanical mixers and would be expected to extend the operational life of the mixers.